PEMBERDAYAAN MASYARAKAT PESISIR MELALUI PELATIHAN MEMBUAT KERUPUK RENGGINING CUMI-SINGKONG BERBASIS AGROMARITIM DI KABUPATEN BANGKA - Sudirman Adibrata; Lizha Dwi Mulya Putri; Dinda Mardiani Lubis; Siti Fatimah (Universitas Mataram, 2026)
The coastal communities of Bangka Regency rely heavily on local resources, including marine fisheries and agricultural commodities. Besides being sold fresh, these commodities can also be processed into downstream products, such as renggining crackers. The purpose of the PKM activity is to empower the community by improving the skills of partners in making innovative squid-cassava renggining crackers. This activity was carried out from June to September 2025 at partner locations, namely Yayasan Lentera Orientasi Nusantara untuk Generasi Edukatif (Longe Foundation) in Balunijuk Village and SMAN 1 Merawang in Baturusa Village, Bangka Regency. The activity method was implemented using a Participatory Action Research (PAR) approach that emphasizes the active involvement of partners in every stage of the program. The training stages start from preparing ingredients, making dough, molding, steaming, drying, frying, to packaging. The results showed that technical training activities and demonstrations or direct practice related to the process of making squid-cassava renggining crackers were well understood by partners. Knowledge transfer to partners regarding local food processing included the transfer of knowledge, technical skills, and technology. Improving skills in the downstreaming of agricultural, marine, and fishery commodities is a concrete action in the effort to implement the agromaritime concept. Small-scale renggining production can improve partners' knowledge, such as recording costs and business results, developing packaging designs, strengthening entrepreneurial capacity, digital marketing, and local product branding strategies. Fried renggining was tested such as taste, aroma, appearance, texture, and testimonials so that partners were able to make renggining with quality improvements according to input obtained from testimonials. These renggining products also demonstrate increased economic added value, diversifying businesses and income sources, and strengthening the concept of coastal food security. Empowerment through an agromaritime approach not only strengthens partners' technical capacity but also leads to the formation of a local entrepreneurial ecosystem. Evaluations conducted in this community service include understanding raw material processing techniques, food sanitation and hygiene, dough formulation, and product packaging and storage techniques.